Influence of donor‐transmitted coronary artery disease on long‐term outcomes after heart transplantation ‐ a retrospective study. (19th December 2020) - Lechiancole, Andrea; Vendramin, Igor; Sponga, Sandro; Sappa, Roberta; Zanuttini, Davide; Spedicato, Leonardo; Ferrara, Veronica; Di Nora, Concetta; Livi, Ugolino
Abstract: Background: Cardiac allograft vasculopathy (CAV) is an important cause of late mortality after heart transplantation, which may be influenced by preexisting coronary disease (CAD) in the donor heart. Methods: The aim of this study was to verify whether CAD in the donor heart had any influence on survival, cardiac‐related adverse events (CRAEs), and coronary disease progression after transplantation. Donor coronary angiography performed in 289 hearts showed absence of CAD in 232 (no‐CAD group) and moderate (≤50%) stenoses (CAD group) in 57. The 2 groups were compared for survival, freedom from CRAEs, and development of grade ≥ 2 CAV after transplantation. Results: Of 30‐day mortality and postoperative complication rate was similar as mean follow‐up (76 ± 56 and 75 ± 55 months) for no‐CAD and CAD ( P  = 0.8). Ten‐year actuarial survival was 58 ± 4% and 62 ± 7% for no‐CAD and CAD ( P  = 0.4). Ten‐year freedom from grade ≥ 2 CAV and from CRAEs was 81 ± 4% and 66 ± 5% vs 75 ± 8% and 67 ± 9% in no‐CAD and CAD ( P  = 0.9 and 0.9, respectively). Conclusions: Donor hearts with moderate CAD did not affect survival, freedom from CRAEs and did not accelerate development of high‐grade CAV after transplantation supporting the use of such grafts to expand the donor pool. Routine use of coronary angiography in donor selection appears justified.